Production of Biodiesel From LGCPO (Low-Grade Crude Palm Oil) Through In-Site Transesterification With The Addition of Catalysts: Produksi Biodiesel dari LGCPO (Low Grade Crude Palm Oil) Melalui Transesterifikasi In-Situ dengan Penambahan Katalis Basa - Rismul Trianto Salawali; Mustika Ibrahim; Mega Fia Lestari (Jurnal Sains dan Teknik Terapan, 2023)
Biodiesel is one of the alternative fuels to replace diesel fuel derived from petroleum. The purpose of this study is to determine the use of LGCPO (low-grade crude palm oil) as biodiesel. Biodiesel preparation is carried out by esterification of 7% H2SO4 catalyst and methanol 1:30 (w/w) at 60 oC for 2 hours. Transesterification was carried out at 60 oC for 1 hour with 1.5% KOH catalyst (w/w) and 35% methanol (w/w). Before synthesizing, the water content obtained was 0.40% and the ALB was 7.46%. Furthermore, specification testing was carried out on biodiesel based on the Indonesian National Standard (SNI) 7182-2015 that has been set, which shows an acid number of 0.4 mg NaOH/gg, density of 860.4 kg/mm3 (simplo) and 866.1 kg/m3 (duplo), and a kinematic viscosity of 2.93 mm2/s at 40 oC.Characterization was carried out by FTIR spectrophotometer analysis, which showed the presence of ester functional groups that are characteristic of synthesized biodiesel: the presence of C-O groups from esters at wavenumbers 1244.13 cm1 and 1170.83 cm1, and the presence of C=O groups from esters at wavenumbers 1743.71 cm1. In addition, Gas Chromatography-Mass Spectroscopy (GC-MS) analysis was also carried out, which showed the presence of six methyl ester (biodiesel) compounds, namely methyl myristate, methyl palmitate, methyl stearate, methyl oleate, methyl linoleate, and methyl arachidate.